Trajectory surface-hopping photoinduced dynamics from Rydberg states of trimethylamine. Issue 18 (29th April 2021) - Pápai, Mátyás; Li, Xusong; Nielsen, Martin M.; Møller, Klaus B.
Abstract : Trajectory surface-hopping simulations reveal the excited-state mechanism of trimethylamine, resonantly pumped to the Rydberg 3p manifold. Key mechanistic aspects are internal conversion and vibrational dynamics occurring on sub-ps and ps timescales. Abstract : We present a computational study on nonadiabatic excited-state dynamics initiated from the 3p Rydberg states of trimethylamine (TMA). We utilise a methodology based on full-dimensional (39 D) trajectory surface-hopping (TSH) simulations, in which propagation is carried out on on-the-fly density functional theory (DFT)/time-dependent DFT (TD-DFT) potentials. Both our electronic structure benchmarks to high-level ab initio methods (EOM-CCSD, CASPT2) and TSH simulations demonstrate high-accuracy of the applied CAM-B3LYP functional for the description of Rydberg excited states. Based on our excited-state simulations, we construct the following mechanistic picture: when pumped resonantly to the 3p Rydberg manifold, TMA coherently vibrates along the planarisation mode with a period of 104 fs and an exponential coherence decay time constant of 240 fs. Nonadiabatic dynamics occur on a faster (∼1 ps) and a slower (∼3 ps) timescale, along the N–C stretching mode by mixing with a dissociative σN–C * state. As a minor relaxation channel, 3p → 3s internal conversion occurs via branching at the σN–C */3s intersection. We find that photodissociaton is hardly observable within 3 ps (1%), which is a failure of the range-separated hybrid CAM-B3LYP functional, as a consequence of its static electron correlation deficiency at long range. In contrast, pure DFT (GGA-BLYP) provides an accurate long-range description (19% dissociation yield), also supported by comparison to recent ultrafast experiments, even if the Rydberg state energies are significantly underestimated (>1 eV). Finally, we reveal the crucial role of vibrational coherence and energy transfer from the planarisation mode for N–C bond activation and resulting nonadiabatic dynamics. The present work illustrates the importance of nuclear–electronic coupling for excited-state dynamics and branching at conical intersections.